If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = -6x + 62 Reorder the terms: 2 + 6x = -6x + 62 Reorder the terms: 2 + 6x = 62 + -6x Solving 2 + 6x = 62 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 2 + 6x + 6x = 62 + -6x + 6x Combine like terms: 6x + 6x = 12x 2 + 12x = 62 + -6x + 6x Combine like terms: -6x + 6x = 0 2 + 12x = 62 + 0 2 + 12x = 62 Add '-2' to each side of the equation. 2 + -2 + 12x = 62 + -2 Combine like terms: 2 + -2 = 0 0 + 12x = 62 + -2 12x = 62 + -2 Combine like terms: 62 + -2 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| 4(x-3)=7x-100 | | 4a×3b/2b×2a | | 1+x=6x+46 | | -10=7x+4x+1 | | 5x^2-125=O | | 11x^2=10x | | 2x+3+6x=67 | | 6y-x=-28 | | 66=2x+6x+2 | | -2x^2-6x+602=0 | | 6x-7+4x=-37 | | 5(8v-6)=8+2v | | 8+x-6x=-47 | | x+(0.18x)=7182.75 | | 9y+2x=35 | | 13x-12-5x=12 | | 7x-3+3x=-53 | | -7+2(3+p)=23+6p | | 1/3x+5=1 | | 3(x-2)+12(x+1)=-24 | | 2thirdsx-7=11 | | 5-5y=-35 | | (-8)+(3*4)-x=0 | | -7(2-8v)=-14+12v | | 5=-4x+7x+5 | | 4+x-3=2x+1-x | | x+35+4x= | | -16-8x=4(-5x+5) | | x+(0.18x)=7503 | | 10-7n=-6(2n+5) | | 2x^2+6x-602=0 | | p+21=3(p+7) |